MAKNA PENDIDIKAN ANAK BAGI KELUARGA PETANI SAWIT DI DESA RAMBAH JAYA KECAMATAN BANGUN PURBA KABUPATEN ROKAN HULU - Weni Hariyati; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Oil palm’s farmers who lives in Rambah Jaya, Bangun Purba subdistric majority only finished elementary school stage because to work as an oil palm’s farmer, they must not finished high level on education. To work as an oil palm’s farmer, see and imitate other person when they work is enough.This research aims to know the sense of children’s education for oil palm’s farmer families and to know parent’s prospects to their child. The problem formulation on this research is ’’ what is the meaning of children’s education for oil palm’s farmer families in Rambah Jaya, Bangun Purba subdistric ? ‘’ Researcher use a qualitative analysis and determine 12 head of household of household (HH) taken intentionally with some criteria. The criteria on taken respondens are the families (parent) with high economic level but have a low children’s education, and families (parent) with low economic level but have a high children’s education.The result of this study show that majority oil palm’s families belief that children’s education is meaningful because children who have an enough education will have a good morals, advanced mindset, help their parent on economic aspect, take up their family’s sosial status, and they can give a motivation to other children in their environment that education is important. The other responden belief that education for children is less meaningful because children have not good enough morals, not good enough mindset and help their parent rarely. The other responden also belief that children’s education is meaningless because children have a bad morals, bad mindset and they won’t help their parent. This study also show that parent hope that their children become a virtous person so they could have high education and have a better future.Keyword : Children education,palm oil and farmer families (parent).